The Relationship Between Soft Drink Consumption Frequency and Screen Time with Overweight Status - I Gusti Made Ari Kartinia Dewi; I Made Suarjana; Ni Made Dewantari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2026)
Overweight is a condition characterized by excessive body fat due to an imbalance between energy intake and expenditure, influenced by genetic, environmental factors, and low physical activity. This fat accumulation increases the risk of non-communicable diseases such as hypertension, stroke, and cancer. Among adolescents, lifestyle factors like frequent soft drink consumption and high screen time contribute to the rising prevalence of overweight. This study aimed to examine the association between the frequency of soft drink consumption and screen time with overweight status among students at SMP Negeri 1 Abiansemal. The study used an observational design with a cross-sectional approach and involved 89 respondents. Data were collected through anthropometric measurements, interviews using the SQ-FFQ, and a screen time questionnaire. The results showed that 37% of students were classified as overweight, while 62.3% were not. Chi-square analysis revealed a significant association between soft drink consumption frequency and overweight status (p = 0.028), but no significant association was found between screen time and overweight status (p = 0.382). Based on these findings, it is recommended that the school provide education on limiting soft drink consumption and screen time as a preventive measure against overweight among adolescents.